Portrait of Relationship between Suppliers and Farmers of Poultry Industry in Special District of Yogyakarta, Indonesia - Syahlani, Suci Paramitasari (2014)
Poultry industry in Indonesia are generally dominated by few and large companies that supply feed, equipment and animal medicine to the farmers. The farmers themselves are dominated by small size farmers who did business for generations and have limited knowledge of both technical and business environments. The number or farmers has attracted more companies in the supply business, caused increasing competition level. Variables those are employed are consumer perceived value, satisfaction toward supplier and trust toward supplier as well as customer loyalty. This research was conducted in the Special Region of Yogyakarta which is one of the centers of poultry farms in Indonesia. The study was conducted with survey design which involved 74 respondents. Respondents were selected by judgmental sampling method with criteria that he/she has minimum 2 years of business experience and has the freedom to determine the supplier of raw materials. Data analysis was conducted with construct validity and reliability testing, hypothesis testing by structural equation modeling. The result showed that consumer perceived value influenced satisfaction toward supplier, while satisfaction toward supplier affected trust toward supplier. However, this research did not showed that both trust and satisfaction toward supplier influenced consumer loyalty.